Prosecution and sentencing patterns in the Federal Republic of Germany - Teske, Raymond H. C. (International criminal justice review, 1992)
Criminal procedure in the Federal Republic of Germany is predicated on an inquisitorial rather than an adversarial system. This paper presents a detailed, step-by-step analysis of the procedures followed in the Federal Republic of Germany from arrest through sentencing, including the options that are available to the prosecutor and the court at each step in the process. Procedures governing the prosecution and sentencing of juveniles and adults are presented. Statistics regarding the offense of robbery are used to illustrate the outcome of the process at each stage as applied to a specific criminal offense. The five categories of robbery in the German Penal Code encompass the full range of possible penalties, including day fine, suspended sentence, imprisonment, and life imprisonment